O Suporte para livros digitais como insumo equiparável ao papel para efeitos tributários: análise de caso do recurso extraordinário 330.817 do STF - LOBO, George Murilo Beckman (2022)
Electronic books along with their supports have become more present nowadays, based on technological advances over time, however, the discussion arose whether, as well as physical books and their basic inputs, e-books and its readers, called e readers, would benefit from cultural tax immunity, with the purpose of reducing their costs and spreading culture through this medium. In this sense, the present work has as object a study on the institute of tax immunity aimed at the constitutional guarantee of access to culture, with the purpose of defending the cheapening of digital book supports from the granting of tax protection, in order to disseminate , more and more, this right through books, through the case study RE 330.817 / RJ. RE 330.817 performed an expansive interpretation of art. 150, VI, “d”, of the Brazilian Federal Constitution, according to the evolution of society, granting tax immunity for digital books and their respective supports, provided that they have the exclusive purpose of reading digital books, ending the judgment with the general repercussion thesis, with the consequent binding summary nº 57.